Analisis Kestabilan Lereng Pada Tanah Timbunan Di Proyek Sekolah Internasional - Merdy Evalina Silaban; M. Fadly Devkha Pratama (Jurnal Pensil : Pendidikan Teknik Sipil, 2025)
The construction of an international school in the Jakarta Garden City area requires additional embankment soil, which creates a potential landslide risk due to elevation differences. This study aims to recalculate the safety of the slope conditions. The results of the analysis of the original slope condition without reinforcement using the Fellenius method yielded a value of 1.239, and this was clarified in the Plaxis analysis with a safety factor value of 1.2445. From these two analyses, the safety factor value is considered unsafe because the minimum safety factor for slope stability is ≥ 1.5 according to SNI 8460:2017 standards. Therefore, several reinforcement alternatives need to be considered. This study uses two reinforcement alternatives: cantilever retaining walls and geotextile reinforcement. The analysis of cantilever retaining walls yielded results of 2.233 for overturning failure, 1.657 for sliding failure, 3 for bearing capacity failure, and a global failure analysis aided by the Plaxis application resulted in 1.9753. All these safety factor values indicate that the retaining wall design is safe. Furthermore, in the stability analysis with geosynthetic reinforcement, a value of 1.556 was obtained, and this was clarified in the Plaxis analysis with a safety factor value of 1.7088. Based on the safety factor results of these two alternatives, the use of cantilever retaining walls is safer.